An online, public health framework supporting behaviour change to reduce dementia risk: interim results from the ISLAND study linking ageing and neurodegenerative disease - Larissa Bartlett; Aidan Bindoff; Kathleen Doherty; Sarang Kim; Claire Eccleston; Alex Kitsos; Eddy Roccati; Jane Alty; Anna E. King; James C. Vickers (BMC, 2023)
Abstract Background Unmanaged cardiometabolic health, low physical and cognitive activity, poor diet, obesity, smoking and excessive alcohol consumption are modifiable health risk factors for dementia and public health approaches to dementia prevention have been called for. The Island Study Linking Ageing and Neurodegenerative Disease (ISLAND) is a dementia prevention public health study examining whether improving knowledge about modifiable dementia risk factors supports behaviour changes that reduce future dementia risk. Methods Residents of Tasmania, Australia, aged 50 + years who joined the 10-year ISLAND study were asked to complete annual online surveys about their knowledge, motivations and behaviours related to modifiable dementia risk. ISLAND included two knowledge-based interventions: a personalised Dementia Risk Profile (DRP) report based on survey responses, and the option to do a 4-week Preventing Dementia Massive Open Online Course (PDMOOC). Longitudinal regression models assessed changes in the number and type of risk factors, with effects moderated by exposures to the DRP report and engagement with the PDMOOC. Knowledge and motivational factors related to dementia risk were examined as mediators of risk behaviour change. Results Data collected between October 2019 and October 2022 (n = 3038, av. 63.7 years, 71.6% female) showed the mean number of modifiable dementia risk factors per participant (range 0 to 9) reduced from 2.17 (SD 1.24) to 1.66 (SD 1.11). This change was associated with the number of exposures to the DRP report (p = .042) and was stronger for PDMOOC participants (p = .001). The interaction between DRP and PDMOOC exposures yielded a significant improvement in risk scores (p = .004). The effect of PDMOOC engagement on behaviour change was partly mediated by increased knowledge (12%, p = .013). Self-efficacy enhanced the effect of knowledge on behaviour change, while perceived susceptibility to dementia mitigated this relationship. Conclusions The ISLAND framework and interventions, a personalised DRP report and the four-week PDMOOC, work independently and synergistically to increase dementia risk knowledge and stimulate health behaviour change for dementia risk reduction. ISLAND offers a feasible and scalable public health approach for redressing the rising prevalence of dementia.